MicroRNA-155 acts as a tumor suppressor in colorectal cancer by targeting CTHRC1 in vitro - Liu, Jingtian (Oncol Lett, 2018)
Colorectal cancer is one of the most common malignancies. Aberrant expressed microRNAs (miRNAs) have been demonstrated to have strong associations with colorectal cancer by repressing their targets. Therefore, miRNAs are thought to have significant promise in the diagnosis and prognosis of colorectal cancer. Previous studies indicated that miR-155 and collagen triple helix repeat containing 1 (CTHRC1) were both involved in pathogenesis of colorectal cancer, but the underlying mechanisms of miR-155 and CTHRC1 are still unknown. The present study aimed to investigate the biological functions of miR-155 and CTHRC1 in colorectal cancer. Reverse transcription-quantitative polymerase chain reaction was used to examine miR-155 and CTHRC1 expression levels. A dual-luciferase reporter assay was applied to verify the target interaction between miR-155 and CTHRC1. Proliferation, cell cycle, apoptosis, cell migration and invasion were measured using the MTT assay, flow cytometry and Transwell assays, respectively. Results showed that miR-155 expression was decreased, but CTHRC1 expression was increased in colorectal cancer tissue and cell lines. Furthermore, it was demonstrated that miR-155 negatively regulated CTHRC1. Additionally, miR-155 overexpression suppressed cell proliferation, induced cell cycle arrest and promoted cell apoptosis, while an inhibitor of miR-155 facilitated cell proliferation and cell cycle and repressed apoptosis. Transwell experiments indicated that miR-155 inhibited the cell migratory and invasive abilities of HT-29 cells, but miR-155 inhibitor enhanced these abilities of HT-29 cells. These results suggested that miR-155 prevented colorectal cancer progression and metastasis via silencing CTHRC1 in vitro, which provides evidence for miR-155 and CTHRC1 as a novel anti-onco molecular target for the treatment of colorectal cancer in the future.